If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9a-4=3(3a-4)
We move all terms to the left:
9a-4-(3(3a-4))=0
We calculate terms in parentheses: -(3(3a-4)), so:We get rid of parentheses
3(3a-4)
We multiply parentheses
9a-12
Back to the equation:
-(9a-12)
9a-9a+12-4=0
We add all the numbers together, and all the variables
8!=0
There is no solution for this equation
| 2x-8=-5x+20 | | -t/4-4=3.1 | | 4.3(-2.1)=z | | 2.5x-3.5+5.1x=3+1.7x | | u-188=264 | | 3/4x+6=3/4(8+x) | | X+3+3x=8x-6 | | -2q+5=2q+1 | | -3(88x-87)+92=90 | | 2x-8=5x+20 | | 50+2.3x=102.2+3.5x | | z+10=14 | | 4x(x-1)=4x-5 | | 12=18-6n | | -28x-14+17x=52 | | z/1=20 | | 7(x-2)=64 | | h/6-2=8.4 | | 7-h=-2h | | 8p-9=5p-5 | | –7y=–4−8y | | 4x+16=4x-12 | | -10+4j=-6j+10 | | 7+x+9=5x+7 | | 5x/2+x=9+3x+10 | | 3p+27=-15 | | -15x(7-1=0 | | 102x-119=17(6x-7) | | 5+14x=3x | | 88,92,87(37x+4)x=90 | | (4x+14)+(5x-5)=90 | | 0.7-y=1.35 |